TECHNICAL EFFICIENCY OF SIAM PATIN FISH CULTIVATION BUSINESS (Case Study of UPT-Islamic University of Riau Kubang Raya, Siak Hulu Sub-District, Kampar District) - Limetry Liana Mey (Jurnal Agribisnis, 2019)
Siam patin fish cultivation in the UPT-UIR is a business-oriented business with the aim of maximizing business profits. Technical efficiency will be achieved if the farmer is able to allocate available production factors to produce high production so that it has an impact on farmer income. This study aims to analyze the allocation of the use of production inputs and the technical efficiency of Siamese catfish cultivation business. This research is a case study on UPT-UIR Pool with the census taking technique of respondents, namely managers and pool workers UPT-UIR. The results showed that the average production costs incurred were worth Rp. 135,321,515.22, consisting of variable costs Rp. 124,713,221.42 (92.16%) and fixed costs Rp. 10,608,293.80 (7.84%). Furthermore, there are 2 types of fish production, namely patin salai and fresh consumption with an average production of 10,628 kg and a selling price of Rp 12,500 / Kg with gross revenues of Rp 132,392,714 / harvest period. Furthermore, the results of the frontier test through 2 trials (approaches) the value of technical efficiency obtained is 0.9873 and 0.4378. Based on the criteria of technical efficiency, the efficiency value <1, means that the allocation of the use of production inputs exceeds the efficiency value so that it is necessary to reduce the use of production inputs. As a result, the business of Siamese catfish in the UPT-UIR Pond is in a technically inefficient condition. In the future, managers must pay attention to the allocation of efficient production inputs not only technically but also allocatively and economically so that they can increase productivity and farmer acceptance.